2018
DOI: 10.1016/j.bioelechem.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

An insoluble iron complex coated cathode enhances direct electron uptake by Rhodopseudomonas palustris TIE-1

Abstract: Microbial electrosynthesis (MES) is a promising bioelectrochemical approach to produce biochemicals. A previous study showed that Rhodopseudomonas palustris TIE-1 can directly use poised electrodes as electron donors for photoautotrophic growth at cathodic potentials that avoid electrolytic H production (photoelectroautotrophy). To make TIE-1 an effective biocatalyst for MES, we need to improve its electron uptake ability and growth under photoelectroautotrophic conditions. Because TIE-1 interacts with various… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…Previously published work from our laboratory, however, suggests no redox active molecule is detectable in the spent-medium 3 . Our laboratory has also shown that a cathode-driven Fe(II)/Fe(III) redox cycle at +100 mV vs. SHE 10 , is also unlikely.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previously published work from our laboratory, however, suggests no redox active molecule is detectable in the spent-medium 3 . Our laboratory has also shown that a cathode-driven Fe(II)/Fe(III) redox cycle at +100 mV vs. SHE 10 , is also unlikely.…”
Section: Discussionmentioning
confidence: 91%
“…In such BESs it is difficult to isolate the response of surface-attached cells. This is because other factors like the influence of planktonic cells 3,10 , extracellular enzymes 26 , and abiotic reactions confound the interpretation of electrochemical data 3,10 . Being able to collect electrochemical data from surface-attached cells exclusively would shed light on whether EEU leads to electron transfer into the pETC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial–electrochemical hybrid systems offer great potential for sustainable upgrading of both CO 2 and N 2 to higher value chemicals. The use of R. palustris TIE-1 in electrosynthetic systems is not new, with prior examples using Fe(II) as a mediator (Doud and Angenent, 2014; Rengasamy et al, 2018) or direct electron transfer (Bose et al, 2014; Rengasamy et al, 2018; Guzman et al, 2019; Ranaivoarisoa et al, 2019). However, there are some inconsistencies with these reports.…”
Section: Discussionmentioning
confidence: 99%